2020
DOI: 10.3390/ijerph17082906
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Digital Health in the Detection and Management of COVID-19

Abstract: Digital health is uniquely positioned to enhance the way we detect and manage infectious diseases. This commentary explores the potential of implementing digital technologies that can be used at different stages of the COVID-19 outbreak, including data-driven disease surveillance, screening, triage, diagnosis, and monitoring. Methods that could potentially reduce the exposure of healthcare providers to the virus are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 24 publications
0
118
0
1
Order By: Relevance
“…This model, as well as being crucial in managing the COVID emergency, provides a template for remote clinical intervention also applicable to future emergencies [11]. The virtual hospital, and its ability to integrate with the regional health system (access to healthcare databases and their integration with the surveillance data, reporting of remotely provided health services), will play a central role in phase two of the epidemic as in-person office visits will have to be reserved for those few cases or single services for which virtual visits are unsuited or ineffective.…”
Section: Resultsmentioning
confidence: 99%
“…This model, as well as being crucial in managing the COVID emergency, provides a template for remote clinical intervention also applicable to future emergencies [11]. The virtual hospital, and its ability to integrate with the regional health system (access to healthcare databases and their integration with the surveillance data, reporting of remotely provided health services), will play a central role in phase two of the epidemic as in-person office visits will have to be reserved for those few cases or single services for which virtual visits are unsuited or ineffective.…”
Section: Resultsmentioning
confidence: 99%
“…Such screening Biometric IoT sensors have already been implemented in several airports around the world, and unlike previous biometric systems that were used primarily for the secure validation of passengers' credentials, they are now focusing on recording detecting data features that can be used to distinguish between healthy and infected passengers. Thermal cameras have been the primary type of biometric IoT sensor that has been chosen by many airports for such detection scenarios [100], [101], as they enable the rapid detection of passengers with high fever without slowing down the screening process, avoiding physical contact which can further spread viruses or requiring more intrusive measures that the passengers may object to. An example of such a camera with thermal capabilities can be seen in Figure 4.…”
Section: Security and Safety Health Systems In Smart Airportsmentioning
confidence: 99%
“…With the proliferation of COVID-19, the threat of worldscale pandemics has become apparent. As a result, added measures of safety and security have been scheduled and implemented in some airports, to detect any cases of infected passengers and reduce the spread of the virus [100]. The primary methods used to screen passengers, prior to boarding is the utilisation of biometric smart sensors, specifically thermal cameras that are configured to raise alarms if the temperature of a passenger exceeds a pre-determined threshold.…”
Section: ) Health Safety Systemsmentioning
confidence: 99%
“…It has been shown that digital approaches in surveillance improve the timeliness and depth of surveillance information in high-income countries [96,97]. So far, DDS has demonstrated its potential in early detection and response to Ebola and COVID-19 epidemics [98][99][100][101]. Recently, DDS has been used in responding to COVID-19 through case detection, contact tracing and isolation, and quarantine in several countries [102].…”
Section: Digital Disease Surveillancementioning
confidence: 99%